Mexico’s Integration into NAFTA Markets : A View from Sectoral Real Exchange Rates and Transaction Costs - Juvenal, Luciana; Blavy, Rodolphe (IMF working paper, 2008)
A self-exciting threshold autoregressive model is used to measure transaction costs that may explain relative price differentials and nonlinearities in the behavior of sectoral real exchange rates across Mexico, Canada and the U.S. Interpreting price threshold bands as transactions costs, we find evidence that Mexico still face higher transaction costs than their developed counterparts, even though trade liberalization lowers relative price differentials between countries. The distance between countries and nominal exchange rate volatility are found to be determinants of transaction costs that limit price convergence. Other factors-including weak domestic competition and transportation-are also likely to be important.
Keywords: North American Free Trade Agreement : (1992 December 17); Foreign exchange rates : Mexico; Foreign exchange rates : United States; Foreign exchange rates : Canada; Investments: Commodities; Exports and Imports; Foreign Exchange; Macroeconomics; Trade Policy; International Trade Organizations; General Financial Markets: General (includes Measurement and Data); Price Level; Inflation; Deflation; Currency; Foreign exchange; International economics; Investment & securities; Real exchange rates; Exchange rates; North American Free Trade Agreement; Arbitrage; Consumer price indexes; Commercial treaties; Financial instruments; Price indexes; North America : Economic integration; United States